Fractal modeling of moisture diffusion in wood cell wall - Dessie T. Tibebu; Stavros Avramidis (Journal of Wood Science)
Abstract Moisture diffusion in wood remains incompletely understood due to its complex hierarchical structure. This study develops a theoretical fractal moisture diffusion model for the wood cell wall, incorporating its structural geometry, and upscales it to bulk wood using electrical resistance modeling and validation. The model accounts for fractal dimensions, porosity, and pore size distribution. Water vapor sorption data, obtained via dynamic sorption, were used to derive experimental diffusion coefficients, while mercury intrusion porosimetry characterized pore size distributions and calculated pore fractal dimensions. Model validation showed that predicted diffusion coefficients aligned with experimental values at low moisture contents. Fractal diffusivity was negatively correlated with pore size ratio and fractal dimensions of pores and tortuosity but positively correlated with porosity. These findings support the development of predictive models for wood geometric properties and moisture diffusivity based on structural attributes.